2019
DOI: 10.30843/nzpp.2019.72.301
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of two types of adhesive for catching insects in traps

Abstract: Sticky traps for monitoring insects use polybutene adhesive (PBA) to entangle insects. This glue is effective but messy to use and an alternative, hot-melt pressure-sensitive adhesive (HMPSA) is available. The effectiveness of these two adhesives was compared for catching pest and beneficial insects, primarily in apples. Various types of trap with either PBA or HMSPA were placed in orchards and vineyards in Hawke’s Bay and Nelson. Eight pests from six families, six parasitoids, five predators and one pollinato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The experiment carried out with different adhesive surfaces indicated that MG is more effective than CG for retaining the captured insect in the traps, preventing their escape. Although CG surfaces are considered easier and cleaner to use than MG [ 30 , 31 ], our results discourage their use in N. rufipes traps. There are few examples in the entomological literature of experiments elucidating the different performances of glues for insect sticky traps.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The experiment carried out with different adhesive surfaces indicated that MG is more effective than CG for retaining the captured insect in the traps, preventing their escape. Although CG surfaces are considered easier and cleaner to use than MG [ 30 , 31 ], our results discourage their use in N. rufipes traps. There are few examples in the entomological literature of experiments elucidating the different performances of glues for insect sticky traps.…”
Section: Discussionmentioning
confidence: 78%
“…(Diptera: Tephritidae) fruit flies in the traps by two different kinds of glue, mentioned as sticky gel (SG) and hot-melt pressure-sensitive adhesive (HMPA). Moreover, Lo et al [ 31 ] evidenced that an HMPA performed better for larger insects (>1.5 mm), while an SG adhesive tended to be more effective for smaller insects. In our observations, we evinced that the ability of N. rufipes to break free from CG adhesive surface seems to be determined not only by its physical characteristics but also by their ability to use their jaws to free their glued legs from the adhesive surface of the hot melt cardboard.…”
Section: Discussionmentioning
confidence: 99%
“…The calculated energies range from −0.57 eV for isobutylene (CH 2 C(CH 3 ) 2 ; Table 2, entry 1) to −4.67 eV for sodium hypochlorite or bleach (NaClO; Table 2,entry 14). Isobutylene was chosen as a representative monomer for polybutene in this study, as polybutene is commonly used as both a bird deterrent applied calcareous statues and architecture 55 and an adhesive added to sticky traps 56 used in the Integrated Pest Management (IPM) programs at many museums. This nonpolar hydrocarbon has the least negative adsorption energy of all of the cleaning agents and common solvents, suggesting that isobutylene, which does not exhibit any hydrogen bonding in its adsorbate−surface interface, does not strongly interact with the calcium-terminated surface and may be safer to use than other molecules in the set.…”
Section: Resultsmentioning
confidence: 99%
“…This information can be interpreted as a measure of the health of the biodiversity in the area. The data produced by light trap catches could shed light on when insects are at their most active [2,[3][4][5]. Light trap data can be used to forecast and predict insect incidence or outbreaks [6].…”
Section: Introductionmentioning
confidence: 99%